Development of Local Wisdom Digital Books to Improve Critical Thinking Skills through Problem Based Learning - Ridho, Shofwan; Wardani, Sri; Saptono, Sigit (Journal of Innovative Science Education, 2021)
The challenge of education entering the 21st century in the era of the industrial revolution 4.0 is expected to get graduates who are competent in utilizing ICT but also competent in developing critical thinking skills. This research aims to develop digital book based on local wisdom to improve critical thinking skills. This research includes Research and Development (R&D) research using ADDIE (Analysis, Design, Development, Implementation, and Evaluation) models. Data analysis techniques used in this study include descriptive data analysis related to the validity and response of users, while to determine the effectiveness of the product used the N-gain test. The results show (1) the developed digital book has valid criteria regarding aspects of the material, presentation, and language (2) students and teachers provide responses to the local wisdom digital book used in learning with response criteria strongly agree (3) assessment results Students' critical thinking skills show improvement with high N-Gain grades. The developed local wisdom digital book is suitable to be used as an alternative source of learning additive material in natural science learning in the face of the 21st century and the industrial revolution 4.0.